Building ecological awareness in coastal elementary schools: The impact of problem-based learning and learning motivation - Roni Alim Ba’diya Kusufa; Linjon Linjon; Yuli Ifana Sari (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2026)
This study aims to examine the influence of the Problem-Based Learning (PBL) model and learning motivation on students’ ecological awareness in social studies education at elementary schools in the coastal area of Cluster II Gending, Probolinggo Regency. A quantitative approach was employed, using a survey of 80 students from five randomly selected elementary schools. Data were collected through validated and reliable questionnaires, supported by observations and interviews. Data analysis used multiple linear regression. Statistical tests showed that the PBL model and learning motivation simultaneously had a significant effect on students’ ecological awareness, with a significance value (Sig) of 0.000 < 0.05 and an R² value of 0.623, indicating that both variables contributed 62.3% to ecological awareness. Partially, the PBL model had a significant effect (Sig = 0.003), as did learning motivation (Sig = 0.001). These findings suggest that the PBL model provides authentic and contextual learning experiences, while learning motivation enhances student engagement and internalization of ecological values. Based on the interview results, ecological awareness is formed not only by conceptual understanding but also by affective factors. The implication is that combining problem-based learning strategies with strengthened learning motivation can serve as a foundation for developing sustainable ecological character through Social Studies education at the elementary level.